A problem of UMCYM

Algebra Level 3

n = 1 2017 ( 1 ) n + 1 n 2 + n + 1 n ! = ? \large \sum_{n=1}^{2017} (-1)^{n+1} \frac{n^2+n+1}{n!} = \ ?

2018 2017 ! + 1 \frac{2018}{2017!}+1 2017 2018 ! 1 \frac{2017}{2018!}-1 2017 2018 ! + 1 \frac{2017}{2018!}+1 2018 2017 ! 1 \frac{2018}{2017!}-1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Kelvin Hong
Jul 21, 2017

n = 1 2017 ( 1 ) n + 1 n 2 + n + 1 n ! \sum\limits_{n=1}^{2017} (-1)^{n+1} \frac{n^2+n+1}{n!}

= n = 1 2017 ( 1 ) n + 1 ( n 2 n ! + n + 1 n ! ) =\sum\limits_{n=1}^{2017} (-1)^{n+1}(\frac{n^2}{n!}+\frac{n+1}{n!})

= n = 1 2017 ( 1 ) n + 1 ( n ( n 1 ) ! + n + 1 n ! ) =\sum\limits_{n=1}^{2017} (-1)^{n+1}(\frac{n}{(n-1)!}+\frac{n+1}{n!})

= ( 1 0 ! + 2 1 ! ) ( 2 1 ! + 3 2 ! ) + ( 3 2 ! + 4 3 ! ) ( 4 3 ! + 5 4 ! ) + . . . ( 2016 2015 ! + 2017 2016 ! ) + ( 2017 2016 ! + 2018 2017 ! ) =(\frac{1}{0!}+\frac{2}{1!})-(\frac{2}{1!}+\frac{3}{2!})+(\frac{3}{2!}+\frac{4}{3!})-(\frac{4}{3!}+\frac{5}{4!})+...-(\frac{2016}{2015!}+\frac{2017}{2016!})+(\frac{2017}{2016!}+\frac{2018}{2017!})

= 1 + 2018 2017 ! =\boxed{1+\frac{2018}{2017!}}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...